Single-cell RNA sequencing in atherosclerosis: Mechanism and precision medicine - Li, Qiaoyu; Wang, Mengchen; Zhang, Shuxia; Jin, Meiqi; Chen, Rongchang; Luo, Yun; Sun, Xiaobo (Frontiers in Pharmacology, 2022)
Atherosclerosis is the pathological basis of various vascular diseases, including those with high mortality, such as myocardial infarction and stroke. However, its pathogenesis is complex and has not been fully elucidated yet. Over the past few years, single-cell RNA sequencing (scRNA-seq) has been developed and widely used in many biological fields to reveal biological mechanisms at the cellular level and solve the problems of cellular heterogeneity that cannot be solved using bulk RNA sequencing. In this review, we briefly summarize the existing scRNA-seq technologies and focus on their application in atherosclerosis research to provide insights into the occurrence, development and treatment of atherosclerosis.